2014
DOI: 10.1627/jpi.57.1
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of Heavy Oil by Hydrogenation through Partial Oxidation and Water-gas Shift Reaction in Supercritical Water

Abstract: Partial oxidation of hydrocarbons including heavy oil in supercritical water forms CO and CO2, which undergoes the water-gas shift reaction to form active hydrogen and then hydrogenation of heavy oil proceeds. In the case of partial oxidation of hydrocarbons and bitumen in supercritical water, the selectivity for partial oxidative products such as CO increased with increasing water density. In the case of hydrogenation of heavy oil in supercritical water through the water-gas shift reaction, reverse water-gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The technique of SCWO is well known, not only because of the destruction of hazardous organic materials into CO2 and H2O [82,83], but also because hydrogenation can proceed without the supply of additional molecular hydrogen [84,85]. In SCW, CO, forming the partial oxidation of hydrocarbon, will undergo a WGS reaction to form in situ hydrogen [85].…”
Section: Partial Scwomentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of SCWO is well known, not only because of the destruction of hazardous organic materials into CO2 and H2O [82,83], but also because hydrogenation can proceed without the supply of additional molecular hydrogen [84,85]. In SCW, CO, forming the partial oxidation of hydrocarbon, will undergo a WGS reaction to form in situ hydrogen [85].…”
Section: Partial Scwomentioning
confidence: 99%
“…The partial SCWO of some model hydrocarbon compounds [84][85][86][87][88][89][90][91] and asphalt [59] showed that the in situ hydrogen is more active than molecular hydrogen in the case of the hydrogenation of hydrocarbon. Sato et al [42] reported the effects of reaction temperature, water/oil ratio, and air pressure as an oxygen source, on the formation of coke.…”
Section: Partial Scwomentioning
confidence: 99%
“…6 shows the ratio of products in the extract oil based on the apparent boiling point ofthe extract oil in SCW + CO.The ratio of oil with an apparent boiling point of less than 423 K increased from 673 to 693 K whereas the ratio of oil with an apparent boiling point of more than 423 K increased from 693 K to 723 K.The lightest extract oil wasobtained at 693 K. Fig. 7showstheproposed upgrading scene occurring inside the reactor forSCW + CO system based on previous studies [8,19,20,22].In the reactor, there is an oil-richphase and a water-rich phase [8,10,13,14,24].The oil inside the reactor isdistributed inthe oil-rich phase and in the water-rich phase, which contains most of the water and gas.The 14 coke precursor, which is a heavy fraction,is mainly presentin the oil-rich phase.If themolecular weight of the heavy fractionincreases substantially by polymerization during the reaction, it will becomeinsoluble in the oil-rich phase, resulting in coke.The presenceof CO 2 in SCW makesthesolvent solubility parameter of SCWsimilar to that of bitumen [20].The effect in the addition of CO toSCW issimilar to the effect CO 2 , although it is difficult to evaluate the solubility of SCW + CO athigh temperatures.Therefore, the introduction of CO,which is less polar than water,toSCW would alsodecrease the polarity of watertothat of bitumen [20].Consequently, the transfer of oil fromthe oil-rich phase to the water-rich phase wasincreased, which facilitated the extraction of oil outside the reactor.Coke formation in SCW + CO was suppressed more than that in SCW becausethe transferof the coke precursor from the oil-rich phase to the water-rich phase was increasedin the presence of CO.Furthermore, we propose that the formation of coke in SCW + CO over along reaction time was similar to that in SCW because the light fraction that can extractthe coke precursor from the oil-rich phase to the water-rich phase was extracted, destabilizing thecoke precursor in the oil-rich phase.…”
Section: Resultsmentioning
confidence: 95%
“…Bitumen recovered by the SAGD method was used for experiments.Distilled waterwas prepared with water distillation apparatus (WG-222, Yamato Co.).CO (99.95%), and H 2 (99.95%) were used as thegases.Toluene (>99.5%) was purchased from Wako Pure Chemical Industries Ltd. Fig.1 shows thesemi-batch type apparatus for upgrading of bitumen.The experiment 7 was similar to that inthe previous study [22].The reactor was made of stainless steel 316 and its volume was 6 cm 3 .Bitumen (1.0 g)was loaded in the reactorandthen the reactor was connected to the pipe from the preheater and the pipeto filter.Water was supplied by an HPLC pump (PU-2086, JASCO) to fill the internal space of the reactor at 30 MPa using a back-pressure regulator (26-1700, Tescom) and the reactor was heated to 573 K, whichbelow the temperature at which the reaction occurred.After the temperatures became stable, the reactor was heated to the reaction temperature, water was re-injected at a flow rate 0.5 or 1.0 g/min, and gas was supplied by a high-pressure syringe pump (ACRAFT, Natori) at 1.110 -3 mol/min.The experimentsperformed by supplying SCW, SCWand CO, and SCWand H 2 are referred to as SCW, SCW + CO, and SCW + H 2 , respectively.It usually took less than30 min to reach the reaction temperature. The reaction time was measuredafter the interiorof the reactor reached the reaction temperature.After the reaction, the reactor was air-cooled, andthe products inside the reactor, and the products in thedownstream line from the reactor, including the receiver, were recovered separately by using toluene.The product in the reactoris defined as the raffinate product and thatin the lines and receiverisdefined as the extract product.Theraffinateproduct was filtered with a 0.1μm membrane filter(ADVANTEC) and separated into the solid and the liquid product.The solid was dried at 333 K 8 overnight and was defined as coke.The toluenesolutionswere evaporated at 353 K under 0.02 MPa to remove tolueneand obtain the recovered oil.The oils derived from the raffinate productand the extract product weredefined as residual oil and extract oil,respectively.In some experiments, the gas produced was sampled and analyzed by gas chromatography with a thermal conductivity detector(GC-2014, Shimadzu).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation